2018
DOI: 10.1101/257048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsupervised embedding of single-cell Hi-C data

Abstract: Single-cell Hi-C (scHi-C) data promises to enable scientists to interrogate the 3D architecture of DNA in the nucleus of the cell, studying how this structure varies stochastically or along developmental or cell cycle axes. However, Hi-C data analysis requires methods that take into account the unique characteristics of this type of data. In this work, we explore whether methods that have been developed previously for the analysis of bulk Hi-C data can be applied to scHi-C data. In this work, we apply methods … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…InnerProduct produced satisfactory projection of the single cells (Fig. 1a), achieving an average area under the ROC curve (AUC) of 0.943, which was as good as original HiCRep reported in the recent work (Liu et al, 2018). The AUCs from fastHiCRep and Selfish were relatively lower (Fig.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…InnerProduct produced satisfactory projection of the single cells (Fig. 1a), achieving an average area under the ROC curve (AUC) of 0.943, which was as good as original HiCRep reported in the recent work (Liu et al, 2018). The AUCs from fastHiCRep and Selfish were relatively lower (Fig.…”
Section: Resultssupporting
confidence: 60%
“…We benchmarked the projection performance and run time of these methods on a recent scHi-C dataset (Nagano et al, 2017), exactly following the evaluation procedure in a recent work (Liu et al, 2018) (Supplementary Note 2). We had following observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a limited number of methods have been developed for the analysis of scHi-C data. We previously developed a similarity-based embedding method called HiCRep/MDS to project scHi-C data into low dimensional space and arrange cells according to their cell-cycle phases [4]. This approach leverages a similarity measure, stratum adjusted correlation coefficient, that was developed for comparing bulk Hi-C matrices [5], combined with multidimensional scaling (MDS) to preserve distances between individual scHi-C contact maps.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that sci-Hi-C is able to separate different cell types on the basis of single cell Hi-C maps and identified previously uncharacterized cell-to-cell heterogeneity in the conformational properties of mammalian chromosomes, enabling "in silico sorting" of mixed cell populations by cell-cycle stage [11][12][13]. We have since improved the initial version of our sci-Hi-C protocol, which is now greatly simplified, easier-to-adapt, and more cost-effective and have successfully applied sci-Hi-C to a diversity of mouse and human cell lines [11][12][13].…”
mentioning
confidence: 99%